2016
DOI: 10.1016/j.ypmed.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in stage of change correlate to changes in dietary intake and clinical outcomes in a 5-year lifestyle intervention in young high-risk Sri Lankans

Abstract: The objectives of a stage-matched approach to lifestyle change are that individuals progress forward through the stages of change. It also posits that progression through the stages of change is associated with positive changes in lifestyle behaviours. Measuring the relationship between stage of change and food intake is challenging due to the plurality of dietary behaviours. Furthermore, it is not clear whether changes in behaviour are sustained long-term. In this study we assess the movement through stages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Studies have shown that better adherence to dietary recommendations has been associated with improvement in the stage of change, self-efficacy and individuals' decisional balance (Guess et al, 2016;Partridge et al, 2017;Steptoe et al, 2003;Tassell and Flett, 2005). Also, with progress in the stage of change, the cons of change decrease and pros increase (Plotnikoff et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that better adherence to dietary recommendations has been associated with improvement in the stage of change, self-efficacy and individuals' decisional balance (Guess et al, 2016;Partridge et al, 2017;Steptoe et al, 2003;Tassell and Flett, 2005). Also, with progress in the stage of change, the cons of change decrease and pros increase (Plotnikoff et al, 2009).…”
Section: Introductionmentioning
confidence: 99%